Exfoliated CrPS4 with Promising Photoconductivity - Budniak, Adam K.; Killilea, Niall Andrew; Zelewski, Szymon J.; Sytnyk, Mykhailo; Kauffmann, Yaron; Amouyal, Yaron; Kudrawiec, Robert; Heiß, Wolfgang; Lifshitz, Efrat (Small, 2019)
Layered semiconductors have attracted significant attention due to their diverse physical properties controlled by composition and the number of stacked layers. Herein, large crystals of the ternary layered semiconductor chromium thiophosphate (CrPS4) are prepared by a vapor transport synthesis. Optical properties are determined using photoconduction, absorption, photoreflectance, and photoacoustic spectroscopy exposing the semiconducting properties of the material. A simple, one-step protocol for mechanical exfoliation onto a transmission electron microscope grid is developed, and multiple layers are characterized by advanced electron microscopy methods, including atomic resolution elemental mapping confirming the structure by directly showing the positions of the columns of different elements' atoms. CrPS4 is also liquid exfoliated, and in combination with colloidal graphene, an ink-jet-printed photodetector is created. This all-printed graphene/CrPS4/graphene heterostructure detector demonstrates a specific detectivity of 8.3 x 10(8) (D*). This study shows a potential application of both bulk crystal and individual flakes of CrPS4 as active components in light detection, when introduced as ink-printable moieties with a large benefit for manufacturing.
CRIS-Team WoS Importer:2019-12-13